Implementasi Pembelajaran Online di Era Pandemi Covid-19: Tantangan dan Peluang - Mila Chrismawati Paseleng; Herry Sanoto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
The World Health Organization (WHO) stated that COVID-19 was a pandemic that has spread to all countries in the world. It has resulted on limited interaction activities and social groups meetings. The education sector is directly affected by the policy of limiting community physical interaction, so that the learning process is fully transformed into the form of online learning. The purpose of this research is to find out the challenges and opportunities in the online learning process that has been implemented during the covid-19 pandemic. The method in this study is a descriptive qualitative research method by describing the online learning process that has been implemented. The subjects in the study were students and teachers of Satya Wacana Lab High School Salatiga. Analysis of the data used in this study is to triangulate data consisting of data from observations, interviews and field observations. The results of the study showed that the online learning process had challenges in terms of the availability of qualified technology such as electronic devices in the learning process, internet networks, and students’ and teachers’ readiness in facing online learning. While the opportunities from the online learning process that have been implemented are directly familiarizing students to practice independently in the learning process, and from the teacher's side, encouraging teachers to master technology and innovate in the learning process so that it would be more varied and effective.